The use of quantitative ultrasound on the finger to detect osteoporosis - Minnock, Enda (Cranfield University, 2011)
The current demand on densitometry services has led to many patients at risk waiting long periods of time, while other healthy individuals are scanned unnecessarily. This work sets out to address the issue of pre-screening for DXA in a postmenopausal population. With simple pen and paper assessments possible, the most important risk factors were selected based on comparison with actual DXA T-Scores. This enabled the creation of a very simple tool that may aid with the prioritisation of those most in need of investigation. The success of commercial QUS devices prompted the inclusion of a number of ultrasound measurements. When added to the simple tools the performance markedly improved. Other known QUS parameters used at the proximal phalanx demonstrated very weak links, if any, with DXA measurements suggesting they may not be useful when it comes to screening large numbers of people. Energy measurements of the phalanx were shown to be correlated to cortical thickness. As cortical thinning is known to advance as osteoporosis worsens, these measurements are proposed as a method of predicting those with low bone mineral density. Further examination found that the thickness was related to density at the neck of femur. This strengthens the claim that energy measurements may accurately choose those requiring immediate intervention.